2012
DOI: 10.1371/journal.pone.0035571
|View full text |Cite
|
Sign up to set email alerts
|

Abundances of Iron-Binding Photosynthetic and Nitrogen-Fixing Proteins of Trichodesmium Both in Culture and In Situ from the North Atlantic

Abstract: Marine cyanobacteria of the genus Trichodesmium occur throughout the oligotrophic tropical and subtropical oceans, where they can dominate the diazotrophic community in regions with high inputs of the trace metal iron (Fe). Iron is necessary for the functionality of enzymes involved in the processes of both photosynthesis and nitrogen fixation. We combined laboratory and field-based quantifications of the absolute concentrations of key enzymes involved in both photosynthesis and nitrogen fixation to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 89 publications
7
44
0
Order By: Relevance
“…Marked regional differences in N 2 fixation are also observed (15) and, in combination, such observations have been argued to support the hypothesis that diazotrophy can be enhanced in regions of high-Fe inputs, resulting in subsequent drawdown of DIP (12,13,16). Although an ever-growing body of evidence supports the importance of Fe for diazotrophy (9,12,14,17), artificial in situ tests comparable to those that unequivocally demonstrated the Fe limited status of high-nitrate low-chlorophyll (HNLC) regions (18) have yet to be performed. Indeed, the slow response timescales of some diazotrophs may ultimately render such experiments unfeasible (19,20).…”
mentioning
confidence: 74%
“…Marked regional differences in N 2 fixation are also observed (15) and, in combination, such observations have been argued to support the hypothesis that diazotrophy can be enhanced in regions of high-Fe inputs, resulting in subsequent drawdown of DIP (12,13,16). Although an ever-growing body of evidence supports the importance of Fe for diazotrophy (9,12,14,17), artificial in situ tests comparable to those that unequivocally demonstrated the Fe limited status of high-nitrate low-chlorophyll (HNLC) regions (18) have yet to be performed. Indeed, the slow response timescales of some diazotrophs may ultimately render such experiments unfeasible (19,20).…”
mentioning
confidence: 74%
“…We therefore summarize cautiously that the increase of fixation at higher latitudes is likely to be caused by unicellular fixation, while Trichodesmium is the prime candidate at lower latitudes. Iron conservation strategies by unicellular diazotrophs have been shown to provide an ecological advantage in low-iron environments of the open ocean (Saito et al 2011), whereas protein level responses of Trichodesmium under iron starvation have been shown to down-regulate N 2 fixation rates (Richier et al 2012). The trace level iron additions during our experiments ranged between 10 and 17 nmol l −1 and although these concentrations are at the lowest end of those reported by Richier et al (2012), it is important to keep in mind how iron availability influences the physiology and the adjacent fixation of N 2 of diazotrophs (Berman-Frank et al 2007, Rubin et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Samples from cultures of Thalassiosira oceanica and Emiliania huxleyi at selected iron and light treatments (see below) were analysed in duplicate for the PSII protein PsbA (D1). PsbA was quantified by immunoblotting as described previously , Richier et al 2012, Ryan-Keogh et al 2012.…”
Section: Determination Of Heme Bmentioning
confidence: 99%
“…In particular, hemoproteins facilitate the 2 most fundamental processes in biology: respiratory and photosynthetic electron transfer via b-and ctype cytochromes (Mochizuki et al 2010). However, knowledge of the abundance of hemoproteins in phytoplankton and their distribution in the marine environment is currently very limited (Gledhill 2007, Saito et al 2011, although it has been shown that low iron concentrations result in reduced abundance of other iron proteins in phytoplankton (Bibby et al 2009, Marchetti et al 2009, Saito et al 2011, Richier et al 2012.…”
Section: Introductionmentioning
confidence: 99%